Diagnostic role of magnetic resonance imaging in assessing orofacial pain and paresthesia - Ohba, Seigo; Yoshimura, Hitoshi; Matsuda, Shinpei; Kobayashi, Junichi; Kimura, Takashi; Aiki, Minako; Sano, Kazuo (The Journal of craniofacial surgery, 2014)
The aim of this study was to compare the efficacy of CT and MRI in evaluating orofacial pain and paresthesia. A total of 96 patients with orofacial pain and/or paresthesia were included in this study. The patients who underwent CT and/or MRI examinations were assessed, and the efficacy of CT and/or MRI examinations in detecting the causative disease of the orofacial pain and paresthesia was evaluated. Seventy (72.9%) of 96 patients underwent CT and/or MRI examinations. Whereas CT examinations detected 2 diseases (4.5%) in 44 tests, 13 diseases (37.1%) were detected in 35 MRI examinations. Seven (53.8%) of 13 diseases, which were detected by MRI, were found in elderly patients. A high percentage of patients, who claimed orofacial pain and paresthesia, have other diseases in their brain, especially in elderly patients, and MRI is more useful than CT for evaluating these patients.